Penerapan Akuntansi Manajemen Dalam Pengambilan Keputusan Bisnis - Inayah Rahma Sari; Purwanti (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This research seeks to evaluate the influence of implementing management accounting on budget planning and cost management in organizations. Management accounting is essential for delivering precise and pertinent information that aids in strategic decision-making, especially regarding budget development and the control of operational expenses. The study utilizes a quantitative approach, gathering data via surveys distributed to manufacturing firms in Indonesia. The findings reveal that optimal management accounting implementation significantly affects the accuracy of budget planning and the efficiency of cost management. Moreover, management accounting helps companies identify cost-saving opportunities and optimize resource utilization. This research highlights the importance of comprehensive management accounting adoption to enhance financial performance through more effective budgeting and efficient cost control.